To appoint shariah committee member as an independent non-executive director of Islamic banks in Malaysia: issues and challenges - Hussain, Mohammad Azam; Hassan, Rusni; Azhar, Alias (2016)
Shariah compliance is a vital element in the operation of Islamic banking business carried out by Islamic banking institutions.In order to strengthen the Shariah governance, the existing legislations regulating Islamic banking business in Malaysia encourage the Islamic financial institutions and Islamic banks in particular, to appoint a member of its Shariah committee (SC) as a member of the Board of Directors (BoD).This article scrutinizes on this issue and the challenges which probably faced by the appointed SC member as member to the BoD of Islamic Financial Institutions.The study found that the suggestion is good to bridge the gap between the SC and the BoD in ensuring Shariah compliance. However it also may invite several legal conflicts and challenges to be faced by the appointed Shariah member if the Islamic banks.